Business Executives’ Perceptions of Ethical Leadership and Its Development - Marsh, Catherine (2013)
This paper summarized the findings of a qualitative study that examines the perceptions of ethical leadership held by those who perceived themselves to be ethical leaders, and how life experiences shaped the values called upon when making ethical decisions. The experiences of 28 business executives were shared with the researcher, beginning with the recollection of a critical incident that detailed an ethical issue with which each executive had been involved. With the critical incident in mind, each executive told the personal story that explained the development of the values he or she called upon when resolving the ethical issue described. The stories were analyzed through the use of constant comparison, which resulted in the development of two models: (1) a framework for ethical leadership illuminating valued aspects of ethical leaderships and the value perspectives called upon when making ethical decisions, and (2) a model explaining how the executives’ ethical frameworks developed. The paper concludes with a brief discussion on virtue ethics, experiential learning, and human resource development.
Keywords: Action Learning; Leadership; Virtue; Ethics